1999
DOI: 10.2307/2463655
|View full text |Cite
|
Sign up to set email alerts
|

Life-History Consequences of Divergent Selection on Egg Size in Drosophila melanogaster

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 10 publications
4
32
1
Order By: Relevance
“…The list of candidate genes identified by Jha and colleagues promises to lay the foundation for further studies that can elucidate the genetic basis of egg-size variation in D. melanogaster. Schwarzkopf et al (1999) selected D. melanogaster for large and small egg size relative to female body size, and found that egg size responded strongly in both directions. Surprisingly, a negative correlation between absolute egg size and fecundity was observed in the large-egg selected line but not in the small-selected lines or the control (without selection).…”
Section: Genetic Controls On Offspring Size and Fecundity In Animals:mentioning
confidence: 99%
See 1 more Smart Citation
“…The list of candidate genes identified by Jha and colleagues promises to lay the foundation for further studies that can elucidate the genetic basis of egg-size variation in D. melanogaster. Schwarzkopf et al (1999) selected D. melanogaster for large and small egg size relative to female body size, and found that egg size responded strongly in both directions. Surprisingly, a negative correlation between absolute egg size and fecundity was observed in the large-egg selected line but not in the small-selected lines or the control (without selection).…”
Section: Genetic Controls On Offspring Size and Fecundity In Animals:mentioning
confidence: 99%
“…In recent decades, a few comprehensive reviews have evaluated the differences in seed size in the context of variation (a) within species , (b) amongst plant functional groups (Westoby et al, 1992;Coomes and Grubb, 2003), (c) in the productivity of crop plants (Sadras, 2007), (d) in mechanisms of dormancy and germination (Rees, 1996;Finch-Savage and Leubner-Metzger, 2006), and the consequences of these differences for the evolution and diversification of seed plants (Leishman et al, 2000;Moles et al, 2005;Linkies et al, 2010). Similarly, among animals, a negative correlation between offspring size and number (fecundity) is widespread across evolutionary scales-(a) within individuals, (b) among individuals of a population, (c) across populations, and (d) across species and higher-level taxonomic groups-thus there is robust evidence for a tradeoff between offspring size and number (Lawlor, 1976;Berrigan, 1991;Sinervo and Licht, 1991;Roff, 1992;Stearns, 1992;Clarke, 1993;Carrière and Roff, 1995;Mckee and Ebert, 1996;Guntrip et al, 1997;Schwarzkopf et al, 1999;Ernsting and Isaaks, 2000;Fox and Czesak, 2000;García-Barros, 2000a,b;Fischer and Fiedler, 2001;Kolm et al, 2006b). …”
Section: Introductionmentioning
confidence: 99%
“…Likewise in D. melanogaster , artificial selection for larger eggs reduces female fecundity (Schwarzkopf et al. 1999). Larger egg size within this species has been associated with larger hatching larvae and faster developmental rate, but not with adult body size (Azevedo et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, much less attention has been paid to the underlying genetic relationship. The few studies available on this subject have not yielded conclusive evidence because the expected trade‐off could at least sometimes not be verified (Schwarzkopf, Blows & Caley, 1999; Fischer et al ., 2006), or its magnitude strongly depended on environmental conditions (Czesak & Fox, 2003). One reason for expected trade‐offs being obscured may be due to variation in total reproductive effort among females, either through variation in the amount of stored resources or through variation in availability and/or acquisition of current feeding (Van Noordwijk & De Jong, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the evolution of offspring size and number and the evolution of total reproductive effort have been explored as separate problems (Smith & Fretwell, 1974; Begon & Parker, 1986; McGinley, Temme & Geber, 1987). The fundamental idea of an independent optimization of offspring size and total reproductive effort in a two‐step process, however, with the decision about optimal reproductive effort being followed by the decision about the optimal partitioning of that investment into few large vs. many small offspring, has been questioned (Winkler & Wallin, 1987; Sinervo et al ., 1992; Bernardo, 1996; Schwarzkopf et al ., 1999; Einum & Fleming, 2000; Caley, Schwarzkopf & Shine, 2001; Czesak & Fox, 2003). At least one model predicts an evolutionary link between both traits (Winkler & Wallin, 1987), and there is some limited support for this notion (Schwarzkopf et al ., 1999; Caley et al ., 2001; Czesak & Fox, 2003).…”
Section: Introductionmentioning
confidence: 99%